Memorandum of understanding between Universiti Teknologi MARA and EMB Business Sdn Bhd / Fakulti Kejuruteraan Kimia - Universiti Teknologi MARA, Fakulti Kejuruteraan Kimia (Universiti Teknologi MARA (UiTM), 2021)
EMB and UiTM are collaborating in a joint-venture project where UiTM as the advisor of the project.